GLUCOSIDASE INHIBITORY ACTIVITY AND IN VITRO FREE RADICAL SCAVENGING ACTIVITY OF ETHYL ACETATE EXTRACTS OF ENDOPHYTES ISOLATED FROM THE ROOT OF CATHARANTHUS ROSEUS.L - ISABELLA ROSALINE, S.; AGASTIAN, P. (International Journal of Pharma and Bio Sciences, 2013)
In this study, the ethyl acetate extracts of EPF and EPA isolated from the root of Catharanthus roseus were studied for its alpha glucosidase inhibitory activity and radical scavenging activity. The ethyl acetate extract showed more α-Glucosidase inhibition (83.29 ± 0.02) at 1000 µg/ml than EPF. Further, oral administration of EPA extract prevents the increase in plasma glucose levels significantly 60 minutes after the maltose and sucrose load at 500mg/kg.b.w concentration, which is equal to acarbose. At 500µg/ml and 1000µg/ml concentration, the EPF extract had shown an inhibition percentage for DPPH scavenging assay 47.59 ± 0.37 and 54.50 ± 0.31 respectively, when compared to EPA extract. The inhibition of DPPH radical by the EPF extracts is relatively higher than other extract. It was found that 1000µg/ml of EPA extract scavenged the hydroxyl free radical level to 70.90 ± 0.17 respectively, when compared to the percentage inhibition by EPF. In case of hydrogen peroxide free radical, scavenging assay at 1000µg/ml concentration the EPA extract showed more inhibition (46.84 ± 0.23) when compared to EPF. In case of nitric oxide scavenging assay, the EPA extract inhibited the nitric oxide radical level (48.71 ± 0.29) highly, when compared to EPF, which lowered the H2O2 radical level by 19.96 ± 0.23 respectively. This result suggests that EPA present in C. roseus play a vital role in the antidiabetic effect and further studies in this actinomycetes will yield novel prototypes for treating diabetes mellitus. The EPA extracts also exhibited the inhibiting effect on rat intestinal α-Glucosidase.